Assessment of the Quality of Speech Therapy Practice in Primary Health Care - Silva-Ríos, Angélica Pilar; del Campo Rivas, Manuel Nibaldo (Revista de Investigación en Logopedia, 2022)
The study of quality represents a relevant topic for users, managers and professionals of the health system. The incorporation of speech therapists into Primary Health Care (PHC) makes necessary to investigate the parameters that make up a quality practice from the perspective of service provision. The objective of this study is to validate the content of a quality matrix of speech therapy practice in PHC through expert judgment. Content validity ratio (CVR), Kendal’s (W) coefficient and content validity index (CVI) were calculated. The matrix considered three dimensions: structure, process and results. 84% of the indicators presented a positive CVR. The process and outcome dimensions presented a statistically significant Kendal coefficient (p <0.05). The total CVI of the test was 0.55. The created matrix explores content domains linked to the quality of of speech therapy services in PHC. The study and management of quality represents an opportunity to improve speech therapy practice in PHC.